Effects of single versus bilateral lung transplantation on primary graft dysfunction after lung transplantation - LIU Zijuan，XU Hongyang (Zhongguo linchuang yanjiu)
"Objective To investigate the differences in primary graft dysfunction（PGD）within 72 h post ⁃ surgery between recipients of single lung transplantation and bilateral lung transplantation，and to evaluate the risk factors for the development of PGD. Methods A retrospective cohort study was conducted to systematically collect and analyze clinical data from 175 lung transplant patients who underwent surgery at the Affiliated Wuxi People's Hospital of Nanjing Medical University，from January to December 2023. Patients were divided into single lung transplantation group（n=58）and bilateral lung transplantation group（n=117）based on transplantation type. Baseline demographic characteristics（such as age，gender and underlying disease），perioperative key indicators［including surgery duration，donor lung cold ischemia time，application of extracorporeal membrane oxygenation（ECMO）］，and early postoperative inflammatory markers were compared between two groups. Univariate and multivariate logistic regression analyses were used to identify factors influencing the development of PGD. Kaplan⁃Meier method was used for survival analysis，and log⁃rank test was applied for significance testing of cumulative survival rates. Results The incidence of severe PGD among 175 lung transplant recipients was 25.14%（44/175）. The incidence of PGD was significantly lower in the bilateral lung transplant group than that in the single lung transplant group［66.67%（78/117）vs 86.21%（50/58），χ2=41.330，P＜0.01］，while there was no statistically significant difference in the incidence of severe PGD between the bilateral and single groups（31.03% vs 22.22%，P＞0.05）. Significant differences were observed between the two groups in terms of age，surgery duration，donor lung cold ischemia time，intraoperative and postoperative ECMO application，and postoperative inflammatory markers（P<0.05）. Univariate and multivariate logistic regression analyses showed that compared with single lung transplantation，bilateral lung transplantation reduced the risk of PGD development（OR=0.160，95%CI：0.058⁃0.441，P<0.01）. The 28⁃day mortality of the entire cohort was 13.71%. There was no statistically significant difference in 28 ⁃ day mortality between the single lung transplantation group and the bilateral lung transplantation group（P>0.05）. Survival analysis showed that the severity of PGD was associated with short ⁃ term mortality, and compared with no PGD, PGD grade 1, and PGD grade 2, PGD grade 3 significantly increased the risk of short⁃term death（P<0.05）. Conclusion The incidence of PGD is lower in the bilateral lung transplantation group than that in the single lung transplantation group. Compared with single lung transplantation，bilateral lung transplantation can reduce the overall risk of PGD."